2014
DOI: 10.1097/dad.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma Clinical Behavior

Abstract: As of 2013, keratoacanthomas (KAs) have not been decided on as either a benign or a malignant entity. Originally considered benign epidermal growths, the assertion by Hodak, Jones, and Ackerman that these lesions are truly "an expression of squamous cell carcinoma" (SCC) fueled the controversy and placed some of the biggest names in the field on opposite sides of the issue. Without a clear understanding of the etiology of KAs and without stringent diagnostic criteria, the literature in regard to KA contains sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 107 publications
2
68
0
Order By: Relevance
“…[11][12][13][14] In addition, there is a preponderance of evidence that keratoacanthoma and squamous cell carcinoma have distinct clinicopathological features. 1,2,[5][6][7] The differentially expressed genes and enriched molecular biological pathways that separate keratoacanthoma from normal skin suggest that keratoacanthoma is a neoplasm that may regress due to upregulation in the cell death/apoptosis pathway. Furthermore, we believe that actinic keratoacanthomas should be treated conservatively and hope that our findings will help prevent radical treatments including wide excision, radiotherapy, and neck dissection for this benign involuting squamous neoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] In addition, there is a preponderance of evidence that keratoacanthoma and squamous cell carcinoma have distinct clinicopathological features. 1,2,[5][6][7] The differentially expressed genes and enriched molecular biological pathways that separate keratoacanthoma from normal skin suggest that keratoacanthoma is a neoplasm that may regress due to upregulation in the cell death/apoptosis pathway. Furthermore, we believe that actinic keratoacanthomas should be treated conservatively and hope that our findings will help prevent radical treatments including wide excision, radiotherapy, and neck dissection for this benign involuting squamous neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Others believe that keratoacanthoma is a distinct selfresolving benign squamoproliferative lesion. 1,2,[5][6][7] To investigate the relationship of keratoacanthoma to squamous cell carcinoma and normal skin, we analyzed the gene expression profile of over 47 000 genes using one of the most comprehensive GeneChip microarrays available (human U133 plus 2.0 array) to study differential gene expression between keratoacanthoma and squamous cell carcinoma and keratoacanthoma and normal skin in formalin-fixed and paraffin-embedded tissue.…”
mentioning
confidence: 99%
“…argues strongly for the benign nature of the lesions, citing that of 445 cases studied over time, zero cases of metastasis were reported and no deaths occurred at the hand of the disease. To the contrary, 5.6% of SCCs directly resulted in death [8].…”
Section: Discussionmentioning
confidence: 99%
“…As far as clinical behavior of KA is concerned, only extremely rare cases of metastatic KAs were reported in the literature and a recent meta-analysis on the subject concluded that, when classified with certainty, KAs have a benign, self limited clinical course 26 . However, cSCC can definitely arise from KAs 27 and often it is very difficult to make a certain distinction between the two.…”
Section: Keratoacanthomamentioning
confidence: 99%